Virtual Soil Monoliths: Blending Traditional and Web‐Based Educational Approaches. Issue 1 (4th February 2013) - Krzic, Maja; Strivelli, Rachel A.; Holmes, Emma; Grand, Stephanie; Dyanatkar, Saeed; Lavkulich, Les M.; Crowley, Chris
Abstract : Since soil plays a crucial role in all aspects of global environmental change, it is essential that post‐secondary institutions provide students with a strong foundation in soil science concepts including soil classification. The onset of information technology (IT) and web‐based multimedia have opened new avenues to better incorporate traditional, static educational resources such as soil monoliths into post‐secondary teaching and learning. The objective of this study was to develop an open access, web‐based educational tool entitled "Virtual Soil Monoliths" (VSM) (http://soilweb.landfood.ubc.ca/monoliths/ ), based on a soil monolith collection at the University of British Columbia (UBC), Vancouver, Canada. With 197 monoliths, the UBC collection is the second largest of its nature in Canada, but due to poor storage and displays it has been underutilized in teaching. The VSM tool was developed by a team of scientists, instructional designers, IT specialists, and students and integrated into the Introduction to Soil Science course at UBC to support lectures and laboratory sections on parent material identification and soil classification. Student feedback indicated the VSM tool was helpful in facilitating student achievement of learning objectives related to basic soil classification and soil identification skills. Students used the VSM tool to complete assignments in the Introduction to Soil Science course, and students pointed out that the high‐resolution monolith photographs were the most useful feature of the tool. This study provides a framework for incorporating inventory‐type learning resources into an interactive teaching tool and a "living" educational resource that helps students grasp connections across disciplines.